Outcomes of Fungal Corneal Ulcer with Impending Perforation after Temporary Suture Tarsorrhaphy - Maharjan, Sumit Singh; Pant, Aashish Raj; Joshi, Purushottam; Shrestha, Pranav; Sharma, Ranjana (Nepalese Journal of Ophthalmology, 2022)
Introduction: This study aims to evaluate outcomes and complications of temporary suture tarsorrhaphy (TST) in cases of impending corneal ulcer perforation.Materials and methods: Case records of patients who underwent temporary suture tarsorrhaphy at Mechi Eye Hospital during a period of 18 months were retrospectively evaluated. All the smear positive fungal keratitis with more than 5mm infiltration involving central and/or paracentral cornea with impending corneal perforation were included. Demographic and clinical profile including – visual acuity, indication for temporary suture tarsorrhaphy, duration of signs and symptoms were noted. The outcomes were evaluated after 1 month and 3 months post tarsorrhaphy, in relation with time to epithelial healing, anatomical success rate, best corrected visual acuity, complications associated with non-healing corneal ulcer, number of temporary suture tarsorrhaphy needed and complications of TST. Results: The study included 119 cases of smear positive fungal keratitis with mean age of 51.34 + 15.56 years. In this study, 56.30% of the patients developed epithelial healing at 2 – 4 weeks with mean duration of 23.24 + 12.09 days of temporary suture tarsorrhaphy. Out of 119 patients, the corneal ulcer healed in 84 patients (70.6%), whereas 35 (29.4%) did not heal. Among those with non-healing ulcers, 15 patients (12.6%) had to undergo evisceration. The anatomical success rate was 87.39% which was statistically significant (P = 0.001). Regarding visual outcome, in 62 patients (52.10%) BCVA improved by 2 or more lines, which was statistically significant (P